Asbestosis, laryngeal carcinoma, and malignant peritoneal mesothelioma in an insulation worker. - Fischbein, A (1991)
Asbestos associated diseases consist of both benign and malignant conditions. A rare constellation of asbestosis, laryngeal carcinoma, and malignant peritoneal mesothelioma occurring in a patient with long term occupational exposure to airborne asbestos fibres is presented. The observation illustrates the powerful disease-causing potential of occupational exposure to asbestos. A brief discussion of multiple primary neoplasms associated with exposure to asbestos is also presented.